Optimisation of Radiation Exposure to Gastroenterologists and Patients during Therapeutic ERCP. (26th March 2013) - Alzimami, Khalid; Sulieman, Abdelmoneim; Paroutoglou, Georgios; Potamianos, Spiros; Vlychou, Marianna; Theodorou, Kiki
Abstract : This study intended to optimize the radiation doses for gastroenterologists and patients during therapeutic endoscopic retrograde cholangiopancreatography (ERCP) and to compare the doses based on available data obtained by other researchers. A total of 153 patients were studied in two Gastroenterology Departments, (group A, 111; group B, 42). Thermoluminescent dosimeters (TLD) were used to measure the staff and patients entrance surface air kerma (ESAK) at different body sites. The mean ESAK and effective doses per procedure were estimated to be 68.75 mGy and 2.74 mSv, respectively. Staff was exposed to a heterogonous doses. The third examiner (trainee) was exposed to a high dose compared with other examiners because no shield was located to protect him from stray radiation. Patients and examiners doses were lower compared to the lowest values found in previous studies taking into consideration the heterogeneity of patients and equipment. Staff doses during ERCP are within the safety limit in the light of the current practice.